Plasticizer-driven ionic mobility and electrochemical stability in alginate-PVA proton-conducting electrolytes - Nuraziliana, Muhd Ghazali; Kentaro, Aoki; Nagao, Yuki; Ahmad Salihin, Samsudin (Elsevier Ltd, 2026)
The development of solid polymer electrolytes (SPEs) with enhanced proton conductivity and thermal stability is critical for next-generation energy storage systems. This study explores the effect of ethylene carbonate (EC) plasticization on alginate-poly (vinyl alcohol) (PVA) biopolymer blend electrolytes (BBEs) doped with glycolic acid (GA). FTIR and XPS analyses confirmed strong hydrogen bonding and effective proton dissociation, while XRD showed reduced crystallinity at the optimum composition (4 wt% EC). This composition achieved the highest proton conductivity of 1.20 × 10−4 S cm−1 with the lowest activation energy (0.18 eV). Thermal studies revealed enhanced stability with favorable Tg. Electrochemical analysis demonstrated leaf-like shape CV profiles with specific capacitance of 54.3 F g−1 at 2 mV s−1 and low ESR, confirming stable EDLC behavior. These findings highlight the role of EC in improving ionic transport, structural flexibility, and electrochemical performance, establishing alginate-PVA-GA-EC as a promising proton-conducting electrolyte for energy storage applications.